The effect of motivational music during exercise on the performance of elite female swimmers - Rad, L. S.; Hafezi, F. (European Journal of Experimental Biology, 2013)
Some studies have shown that an exercise session with music can enhance the speed and performance of athletes. The question is whether music is actually effective for athletic performance. The purpose of the present research is to examine the effect of motivational music during exercise on the performance of elite female swimmers. 30 women (18-25 yrs) with average height of 161 cm and average weight of 60 kg participated in the research. Pressure perception was measured using Borg`s Rate of Perceived Exertion Scale, and resting heart rate and heart rate after a 100m swim as well as the time of the 100m swim were measured. The subjects were divided into an experimental group and a control group. Both groups participated in 16 exercise sessions, with the experimental group listening to motivational music, while the control group performed the exercises without any music. Then the participants took the post-test. The data was analyzed using ANOVA in SPSS 19 (P < 0.05). The results showed no significant differences between the studied groups in any of the variables. Listening to motivational music during exercise has had no effect on the performance of elite female swimmers